Transumbilical Single-Site Laparoscopic Intraperitoneal Closure of the Internal Inguinal Ring for Pediatric Inguinal Hernia - Yi Ji; Yanan Li; Xuepeng Zhang; Tong Qiu; Siyuan Chen; Zhicheng Xu (Frontiers Media S.A., 2022)
BackgroundA new novel technique for pediatric inguinal hernia (PIH) repair, namely, transumbilical single-site laparoscopic intraperitoneal closure (TUSLIC) of the internal inguinal ring (IIR) with a single instrument, was introduced. The short-term follow-up of TUSLIC for PIH was compared with that of transabdominal multiple-site laparoscopic extraperitoneal closure (TAMLEC) for PIH.MethodsDescriptive variables, perioperative clinical features, and short-term outcomes were retrospectively analyzed and compared between the patients who underwent TUSLIC and those who underwent TAMLEC.ResultsIn total, 289 patients were enrolled in this study. Of these, 190 patients received TUSLIC, and 99 patients received TAMLEC. The descriptive variables (including sex, age, weight, and preoperative diagnosis of patients) were comparable between the two groups (P-values were 0.12, 0.71, 0.69, and 0.23, respectively). The mean operative times for unilateral hernia repair and bilateral hernia repairs in TAMLEC group were significantly less than those in TUSLIC group (P < 0.01). The values of surgical site infection, umbilical bleeding, testicular atrophy, iatrogenic ascent of the testis, and secondary hydrocele were not significantly different between the two groups. There were no suture granulomas, and recurrence occurred in TUSLIC group, though at a significantly lower rate than in TAMLEC group (P < 0.05).ConclusionsTUSLIC is a feasible, safe, and reliable minimally invasive method for PIH. Compared with TAMLEC, TUSLIC has the advantages of minimized complications and a low recurrence rate.